Ecological Perspective on Architecture: A Study of Arsitektur Nusantara As Adapting Form in Tropical Environment - Agung Cahyo Nugroho (Jurnal Arsitektur, 2023)
Abstract: Arsitektur Nusantara is an architecture product that is highly responsive in overcoming climatic challenges, particularly in the archipelago's tropical environment. This becomes everyone's interest to understand and investigate this phenomenon from various points of view. The extensive migration over space and time to the tropical environment necessitates adaption measures as the fundamental impulses that shape the locality's culture of living. In an ecological viewpoint, the adaptation process of living things includes morphological, physiological, and behavioral adaptations, which are manifested in the results of human thought, including buildings to adapt to local conditions. This adaptive manifestation can also be seen in the traditional building products of the people of nusantara as a product of construction work towards their true values. The method used in this article is a literature review of nusantara architecture which will be compared with aspects of adaptation in the context of tropical ecology. The result show that the form of ecological adaptation is also seen in the shape of the building (structure), building elements (details and construction), the building material, and the attitude/position of the building on the site.